The Impact of Financial Development on Renewable and Non-Renewable Energy Consumption - Polat, Burcak (Energy Economics Letters, 2021)
To date, a sufficient number of studies have dealt with the effect of financial development on energy consumption. Yet, most of these studies have neglected diversification between renewable and non-renewable energy consumption. In fact, financial development may affect renewable energy consumption differently than non-renewable energy consumption. This is because renewable energy production necessitates high-cost investments. Therefore, the main objective of this study is to estimate the impact of financial development on renewable and non-renewable energy consumption in 37 OECD countries by employing the one-step system generalized method of moments (GMM) for the period 2002–2015. The findings statistically proved that financial development is positively linked with renewable energy consumption, but it is not related to non-renewable energy consumption. This paper also confirmed the existence of a negative correlation between the openness index and renewable energy consumption with non-renewable energy consumption. Intuitively, it was expected that renewable energy production engages in high-cost investments compared to non-renewable energy production. Thus, renewable energy consumption is more responsive to a solid and well-structured financial market than non-renewable energy consumption.